2005
DOI: 10.1186/1465-9921-6-89
|View full text |Cite
|
Sign up to set email alerts
|

Global expression profiling of theophylline response genes in macrophages: evidence of airway anti-inflammatory regulation

Abstract: Background: Theophylline has been used widely as a bronchodilator for the treatment of bronchial asthma and has been suggested to modulate immune response. While the importance of macrophages in asthma has been reappraised and emphasized, their significance has not been well investigated. We conducted a genome-wide profiling of the gene expressions of macrophages in response to theophylline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…A number of mediators released from macrophages that play an important role in asthmatic inflammation are implied for their involvement either in the beginning or persisting of inflammation [25,26]. IL-1β, IL-6, IL-8, platelet activating factor (PAF) and tumour necrosing factor α (TNFα) are markers released from macrophages and stimulate many inflammatory cells as well as the production of acute phase proteins [7,9,26]. This stimulation might be the cause of the augmentation of well known acute phase reactant SAA in bronchial tissue.…”
Section: Discussionmentioning
confidence: 99%
“…A number of mediators released from macrophages that play an important role in asthmatic inflammation are implied for their involvement either in the beginning or persisting of inflammation [25,26]. IL-1β, IL-6, IL-8, platelet activating factor (PAF) and tumour necrosing factor α (TNFα) are markers released from macrophages and stimulate many inflammatory cells as well as the production of acute phase proteins [7,9,26]. This stimulation might be the cause of the augmentation of well known acute phase reactant SAA in bronchial tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The CM is a serumfree medium with 24 h incubation with phorbol myristate acetate-treated THP-1 cells. Our previous studies and the other reports showed that the CM might contain proinflammatory cytokines such as tumor necrosis factor-a, IL-1, IL-8, and IL-12; anti-inflammatory cytokines such as transforming growth factor-h, IL-4, IL-10, and IL-13; and IL-6 with both proinflammatory and anti-inflammatory properties (3,11,27,39,40). Previous reports have shown that the imbalance between proinflammatory and anti-inflammatory cytokines can influence neoplastic outcome (3).…”
Section: Discussionmentioning
confidence: 99%
“…It is now believed that the anti-inflammatory effect of theophylline is caused by its ability to inhibit the responses of these proinflammatory cells Barnes, 2003). For example, it has been shown that the therapeutic concentration of theophylline (55-110 M) can significantly inhibit the expression and release of TNF-␣, IL-8, IL-5, and IL-13 from human blood monocytes/alveolar macrophages in vitro (Spatafora et al, 1994;Kimura et al, 2003;Yao et al, 2005). In vivo, the drug has been shown to significantly reduce the number of eosinophils and T cells present in the bronchoalveolar lavage fluid of asthmatics (Kidney et al, 1995;.…”
mentioning
confidence: 99%